Fetal Hemodynamic Response to Anemia in Early Gestation: Using Hemoglobin Bart’s Disease as a Study Model - Luewan, Suchaya; Tongprasert, Fuanglada; Srisupundit, Kasemsri; Traisrisilp, Kuntharee; Jatavan, Phudit; Tongsong, Theera (Ultraschall in der Medizin - European Journal of Ultrasound, 2021)
Objective To assess fetal hemodynamic changes in response to anemia in early gestation, using fetal Hb Bart’s disease as a study model.Methods A prospective study was conducted on pregnancies at risk for fetal Hb Bart’s disease at 12–14 weeks of gestation. Fetal hemodynamics were comprehensively assessed by 2D ultrasound, Doppler velocity, and cardio-STIC just prior to the invasive procedure for diagnosis. The various hemodynamic parameters of the affected and unaffected fetuses were compared.Results Of 56 fetuses at risk, 17 had Hb Bart’s disease and 39 were unaffected. The right and combined ventricular cardiac outputs (CO) were significantly higher in the affected fetuses (0.993 vs. 1.358; p < 0.001 and 1.010 vs. 1.236; p < 0.001, respectively), whereas the left CO tended to be higher but not significantly (1.027 vs. 1.113; p = 0.058). Cardiac dimensions, middle-cerebral artery peak systolic velocity, Tei index, and isovolemic contraction time were significantly increased, while the global sphericity index was significantly decreased. Interestingly, cardiac preload, ventricular wall thickness, shortening fraction, isovolemic relaxation time, and fetal heart rate were unchanged. Four fetuses had hydropic changes, but all cardiac functions were normal.Conclusion Fetal anemia induces hypervolemia and increases cardiac output to meet the tissue oxygen requirement, resulting in an increase in size without hypertrophy, volume load without pressure load, and a decrease in the globular sphericity index. The heart works very well but works harder, especially systolic ventricular load. Hydrops fetalis due to anemia appears not to be caused by heart failure as previously believed but rather by volume load with high vascular permeability at least in early pregnancy.
Keywords: anemia; fetus; hemoglobin Bart’s disease; hydrops fetalis; ultrasound